2015
DOI: 10.1039/c5nr02588e
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the defect state and reducibility of ceria based nanoparticles for improved anti-oxidation performance

Abstract: Due to their excellent anti-oxidation performance, CeO2 nanoparticles receive wide attention in pharmacological application. Deep understanding of the anti-oxidation mechanism of CeO2 nanoparticles is extremely important to develop potent CeO2 nanomaterials for anti-oxidation application. Here, we report a detailed study on the anti-oxidation process of CeO2 nanoparticles. The valence state and coordination structure of Ce are characterized before and after the addition of H2O2 to understand the anti-oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 64 publications
3
101
0
Order By: Relevance
“…Physical properties of nanoceria play a decisive role of its antioxidative property ( Figure 10 [55,56], but also regulate its unique optical properties, which made it possible to study the molecular mechanism of intracellular signaling transduction in a living cell induced by nanoceria and adjust antioxidant properties of nanoceria.…”
Section: Hot Topics and Challenges Of Nanoceria In Antioxidant Therapymentioning
confidence: 99%
“…Physical properties of nanoceria play a decisive role of its antioxidative property ( Figure 10 [55,56], but also regulate its unique optical properties, which made it possible to study the molecular mechanism of intracellular signaling transduction in a living cell induced by nanoceria and adjust antioxidant properties of nanoceria.…”
Section: Hot Topics and Challenges Of Nanoceria In Antioxidant Therapymentioning
confidence: 99%
“…Since the reaction mechanism strongly depends upon the pH of the reaction, 7,18 this method allows reliable quantitative evaluation of reaction species in ceria samples. 11,19,20 Our study revealed reversible changes in the oxidation states of cerium and local atomic structures of ceria in the H 2 O 2 disproportionation reaction. In our experiments, ceria nanorods were first added to a solution containing 10 mM H 2 O 2 and 0.1 M Tris buffer (pH = 7.54) to yield a reaction mixture with a nanorod concentration of 500 mg L À1 .…”
mentioning
confidence: 64%
“…Our finding corroborated similar observations of pH reduction by Wang et al in their study of H 2 O 2 disproportionation catalyzed by nanoceria. 11 As the reaction proceeded, the concentration of H 2 O 2 decreased and ceria nanorods possessed significant population of Ce 3+ on their surfaces. These two factors led to changes in solution potential and ceria surface potential, which consequently promoted the oxidation of Ce 3+ to Ce 4+ by H 2 O 2 molecules (eqn (2)).…”
mentioning
confidence: 96%
“…X‐ray photoelectron spectroscopy (XPS) core‐level spectra of the elements found over the catalyst surface after reduction at 420 °C in H 2 are presented in Figure (a detailed characterisation of the pristine samples is shown in Figure S1). For the quantification of the data, the collected Ce 3d high‐resolution spectra (Figure a) were curve fitted with a combination of two reference spectra of Ce IV and Ce III recorded over cerium(IV) oxide and hexahydrate cerium(III) nitrate, as suggested previously . The peak fitting procedure is presented in Figure S2.…”
Section: Resultsmentioning
confidence: 99%